Trans-Graft Protection Against Pierce’s Disease Mediated by Transgenic Grapevine Rootstocks - Dandekar, Abhaya M.; Jacobson, Aaron; Ibáñez, Ana M.; Gouran, Hossein; Dolan, David L.; Agüero, Cecilia B.; Uratsu, Sandie L.; Just, Robert; Zaini, Paulo A. (Frontiers in Plant Science, 2019)
A field study showed that transgenic grapevine rootstocks can provide trans-graft-mediated protection to a wild type scion against Pierce’s disease (PD) development. We individually field-tested two distinct strategies. The first expressed a chimeric antimicrobial protein (CAP) that targeted the functionality of the lipopolysaccharide (LPS) surface of Xylella fastidiosa, the causative agent of PD. The second expressed a plant polygalacturonase inhibitory protein (PGIP) that prevents PD by inhibiting breakdown of pectin present in primary cell walls. Both proteins are secreted to the apoplast and then into the xylem, where they migrate past the graft union, transiting into the xylem of the grafted scion. Transgenic Vitis vinifera cv. Thompson Seedless (TS) expressing ether CAP or PGIP were tested in the greenhouse and those lines that showed resistance to PD were grafted with wild type TS scions. Grafted grapevines were introduced into the field and tested over seven years. Here we present data on the field evaluation of trans-graft protection using four CAP and four PGIP independent rootstock lines, compared to an untransformed rootstock. There was 30 to 95% reduction in vine mortality among CAP- and PGIP-expressing lines after three successive yearly infections with virulent X. fastidiosa. Shoot tissues grafted to either CAP or PGIP transgenic rootstocks supported lower pathogen titers and showed fewer disease symptoms. Grafted plants on transgenic rootstocks also had more spring bud break following infection, more shoots, and more vigorous growth compared to those grafted to wild type rootstocks. No yield penalty was observed in the transgenic lines and some PGIP-expressing vines had enhanced yield potential. Trans-graft protection is an efficient way to protect grape scions against PD while preserving their valuable varietal genotypes and clonal properties.